Stroke in the adult Qatari population (Q-stroke) a hospital-based retrospective cohort study - Yahia Z. Imam (9401836) (2020)
Background Studies assessing the burden of stroke in Qataris are limited. We aim to study stroke in the Qatari population. Methods A retrospective review was undertaken of all Qatari adults presenting with stroke to Hamad Medical Corporation over a 5-year period. Descriptive statistics were used to summarize demographic and all other clinical characteristics of the patients. The primary outcome was the incidence of stroke in the Qatari patients. Comparison was made between the sexes. Results 862 patients were included, with 58.9% being male. The average incidence of stroke over the 5-year period was 92.04 per 100,000 adult Qatari population. The mean age of the cohort was 64.3±14.4 years, (range 19–105 years). The mean age of first ever cerebrovascular event was 63.2±14.5 years. The diagnosis was ischemic stroke in (73.7%), transient ischemic attack in (13.8%), intracerebral hemorrhage (ICH) in (11.6%), subarachnoid hemorrhage in (0.7%) and (0.2%) cerebral venous sinus thrombosis. Small vessel disease was the most common cause of ischemic stroke accounting for (46.5%), followed by large artery atherosclerosis (24.5%). Hypertension (82.7%) and diabetes (71.6%) were particularly prevalent in this cohort. Females were older (65.8±14.1 vs 63.4±14.5 years), had more hypertension and diabetes and more disability or death at 90 days (p<0.05) compared to Qatari males. Conclusion Stroke occurs at a significantly lower age in Qataris compared to the western population. This study has uncovered sex differences that need to be studied further. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0238865